Transient Hypothyroidism During Lactation Arrests Myelination in the Anterior Commissure of Rats. A Magnetic Resonance Image and Electron Microscope Study - Federico S. Lucia; Jesús Pacheco-Torres; Susana González-Granero; Santiago Canals; María-Jesús Obregón; José M. García-Verdugo; Pere Berbel (Frontiers Media S.A., 2018)
Thyroid hormone deficiency at early postnatal ages affects the cytoarchitecture and function of neocortical and telencephalic limbic areas, leading to impaired associative memory and in a wide spectrum of neurological and mental diseases. Neocortical areas project interhemispheric axons mostly through the corpus callosum and to a lesser extent through the anterior commissure (AC), while limbic areas mostly project through the AC and hippocampal commissures. Functional magnetic resonance data from children with late diagnosed congenital hypothyroidism and abnormal verbal memory processing, suggest altered ipsilateral and contralateral telencephalic connections. Gestational hypothyroidism affects AC development but the possible effect of transient and chronic postnatal hypothyroidism, as occurs in late diagnosed neonates with congenital hypothyroidism and in children growing up in iodine deficient areas, still remains unknown. We studied AC development using in vivo magnetic resonance imaging and electron microscopy in hypothyroid and control male rats. Four groups of methimazole (MMI) treated rats were studied. One group was MMI-treated from postnatal day (P) 0 to P21; some of these rats were also treated with L-thyroxine (T4) from P15 to P21, as a model for early transient hypothyroidism. Other rats were MMI-treated from P0 to P150 and from embryonic day (E) 10 to P170, as a chronic hypothyroidism group. The results were compared with age paired control rats. The normalized T2 signal using magnetic resonance image was higher in MMI-treated rats and correlated with the number and percentage of myelinated axons. Using electron microscopy, we observed decreased myelinated axon number and density in transient and chronic hypothyroid rats at P150, unmyelinated axon number increased slightly in chronic hypothyroid rats. In MMI-treated rats, the myelinated axon g-ratio and conduction velocity was similar to control rats, but with a decrease in conduction delays. These data show that early postnatal transient and chronic hypothyroidism alters AC maturation that may affect the transfer of information through the AC. The alterations cannot be recovered after delayed T4-treatment. Our data support the neurocognitive delay found in late T4-treated children with congenital hypothyroidism.